(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
On the basis of the scientific research conducted on the development of the technology of obtaining facade liquid wallpaper on the basis of fibrous waste of enterprises producing carpets and carpet products, its comparison with existing analogues in the world is considered characteristic.